2019
DOI: 10.1038/s41598-019-56126-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of hematogones and CD34+ myeloblasts in bone marrow for adult B-cell lymphoblastic leukemia without minimal residual disease

Abstract: This study was aimed to dissect the prognostic significances of hematogones and CD34+ myeloblasts in bone marrow for adult B-cell acute lymphoblastic leukemia(ALL) without minimal residual disease(MRD) after the induction chemotherapy cycle. A total of 113 ALL patients who have received standardized chemotherapy cycle were analyzed. Cases that were not remission after induction chemotherapy or have received stem cell transplantation were excluded. Flow cytometry was used to quantify the levels of hematogones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This value corresponded to the normal range for age in our population, as previously demonstrated in a Brazilian multicenter study 20 . Similar results had been described by other studies concerning MDS 28 , 29 and ALL in remission after induction 30 . Although the decrease of hematogones is considered to be a diagnostic hallmark of MDS, a preserved number in low-risk cases is a sign of a better survival.…”
Section: Discussionsupporting
confidence: 91%
“…This value corresponded to the normal range for age in our population, as previously demonstrated in a Brazilian multicenter study 20 . Similar results had been described by other studies concerning MDS 28 , 29 and ALL in remission after induction 30 . Although the decrease of hematogones is considered to be a diagnostic hallmark of MDS, a preserved number in low-risk cases is a sign of a better survival.…”
Section: Discussionsupporting
confidence: 91%
“…MRD assessment by molecular techniques was not done in our study. Similar to the CD19+ Hgs, the prognostic significance of stage 0 Hgs in MRD negative BCP‐ALL cases shall be studied in future (Arabi et al, 2023; Liao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…5,16,17,20,37 However, the prognostic value of HGs in ALL patients is not well understood. 27,38 In the present study, we investigated the significance of detectable HGs following remission after chemotherapy in childhood ALL. Our results show the independent prognostic value of HGs on RFS after adjustment for other prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The potential prognostic impact of BM HGs has been suggested by recent reports, as previous studies have demonstrated that presence of HGs at the recovery phase was associated with favorable outcomes in patients with AML and patients undergoing HSCT 5,16,17,20,37 . However, the prognostic value of HGs in ALL patients is not well understood 27,38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation